IMPLEMENTASI DIDAKTIK METODIK PEMIKIRAN K.H. HASYIM ASY’ARI DALAM KITAB ‘ADABUL’ALIM WAL MUTA’ALIM DALAM MENINGKATKAN MUTU PENDIDIKAN DI MADRASAH ALIYAH NURUL HIKMAH DAN MADRASAH ALIYAH AL AKBAR BANYUASIN - M. Idrus,; Muhammad Feri Fernadi,; Muhammad Feri Fernadi, (UNISAN JURNAL, 2023)
This study aims to examine the implementation of didactic methodology in the thought of K.H. Hasyim Asy’ari in improving the quality of education at Nurul Hikmah and Al Akbar Islamic Senior High Schools in Banyuasin. The research method used in this study is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study show that the teachers' understanding of didactic methodology in the thought of K.H. Hasyim Asy’ari is good, although there are some weaknesses in its application. The teaching practices carried out by the teachers by applying didactic methodology in the thought of K.H. Hasyim Asy’ari show an improvement in the quality of learning reflected in the critical thinking skills, creativity, and social abilities of the students, which have improved significantly. The impact of implementing didactic methodology in the thought of K.H. Hasyim Asy’ari in improving the quality of education at Nurul Hikmah and Al Akbar Islamic Senior High Schools in Banyuasin is the improvement of students' understanding of the subject matter, critical thinking and creativity skills, as well as their social abilities. This study shows that the implementation of didactic methodology in the thought of K.H. Hasyim Asy’ari can have a positive impact on improving the quality of education at Nurul Hikmah and Al Akbar Islamic Senior High Schools in Banyuasin.